2012
DOI: 10.1177/183693911203700305
|View full text |Cite
|
Sign up to set email alerts
|

Relational aggression and prosocial behaviours in Australian preschool children

Abstract: RELATIONAL AGGRESSION IS A subtle form of aggressive behaviour that uses dyadic relationships and manipulation as a vehicle of harm. Little is known about relational aggression in preschool-age children in cultural contexts outside the United States. This study examined relationally aggressive behaviours and prosocial behaviours in Australian preschoolers. The sample consisted of 60 children aged from three to five years (35 boys, 25 girls). Teachers rated children's social behaviour in terms of relational agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 24 publications
4
33
0
3
Order By: Relevance
“…Thus, the storylines in these texts depict the manipulator as strategic and egoistic, and the manipulated person as the victim of the egocentric intentions of the manipulator. In articles on children and young people as manipulators, the concept often refers to popular children and young people trying to maintain their social status among peers and is associated with aggression and bullying (Barlow et al, 2010;Cillessen and Rose, 2005;Hawley, 2003;Isen et al, 2010;Rose and Swenson, 2009;Swit and McMaugh, 2012). Drawing on the same negative coding of manipulation as a way to promote egoistic goals, Mandal and Kocur (2013) investigate borderline patients' use of manipulation techniques such as simulating symptoms, acting out and being aggressive.…”
Section: Meaning Of Manipulation: Positioning the Manipulator And Thementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the storylines in these texts depict the manipulator as strategic and egoistic, and the manipulated person as the victim of the egocentric intentions of the manipulator. In articles on children and young people as manipulators, the concept often refers to popular children and young people trying to maintain their social status among peers and is associated with aggression and bullying (Barlow et al, 2010;Cillessen and Rose, 2005;Hawley, 2003;Isen et al, 2010;Rose and Swenson, 2009;Swit and McMaugh, 2012). Drawing on the same negative coding of manipulation as a way to promote egoistic goals, Mandal and Kocur (2013) investigate borderline patients' use of manipulation techniques such as simulating symptoms, acting out and being aggressive.…”
Section: Meaning Of Manipulation: Positioning the Manipulator And Thementioning
confidence: 99%
“…Children's manipulative acts: Positioning and its moral implications When children are described as exerting intentional mental influence, these acts are conceptualised either as manipulation or Machiavellianism with negative moral implications (Beeble et al, 2007;Cillessen and Rose, 2005;Finkenauer et al, 2005;Gagné and Bouchard, 2004;Hawley, 2003;Overbeek et al, 2006;Summers and Summers, 2006;Swit and McMaugh, 2012;Walling et al, 2007). None of the articles conceptualize such acts by children in terms of behaviour modification or skilful negotiation, with the exception of Hawley's (2003) article on Machiavellianism, and even less so in terms of treatment, therapy and education as do some articles dealing with adults' attempts to exert intentional mental influence (e.g.…”
Section: Constructions Of Mental Influence As Non-manipulationmentioning
confidence: 99%
“…Positive outcomes include greater academic success (Collie et al, 2018;Gerbino et al, 2018), social competence (Bar-Tal, 1982), and problem-solving skills (Carlo et al, 2012;Eisenberg et al, 2015). Prosocial behaviour is considered a psychosocial asset (Leventhal et al, 2015), that contributes to better quality peer relationships (Caputi et al, 2012), lower reported aggression (Swit, 2012;Obsuth et al, 2015), and favourable subjective well-being (Aknin et al, 2012(Aknin et al, , 2015Proctor and Linley, 2014;Yang et al, 2019). Previous work also suggests that prosocial behaviour was associated with child health-related outcomes and behaviours including fewer externalising and internalising behavioural problems (Flynn et al, 2015;Flouri and Sarmadi, 2016), lower screen time (Healy and Garcia, 2019), and optimal cardiometabolic health (Qureshi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Prososyal davranışlar, sosyalleşme sürecinin bir parçası olmakla birlikte daha ileri bir beceri olarak görülmektedir (MEB, 2013). Birey, toplumun değer yargılarını gözeterek yine toplum tarafından kabul gören davranışları tercih ederek prososyal davranışlar sergilediğinde; bu durum ahlaki gelişimin olumlu yönü olarak ifade edilmektedir (Beaty, 1998 (Swit ve McMaugh, 2012). Diğer bir deyişle çocukların ahlaki ve sosyal kural bilgisi algıları ne kadar arttırılırsa prososyal davranışları daha sık sergileyecekleri ve böylelikle de gösterdikleri saldırganlık türlerinin de azalmış olduğu gözlemlenecektir.…”
Section: Introductionunclassified